Exploring Linguistics Dynamics: Code-Switching and Code Mixing on Selected Video of The Indah G Show - Fasah, Azizzah El; Saehu, Andang; Nurhapitudin, Irman (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study examines the kind and purpose of code-switching and code-mixing in the video of The Indah G Show called “Indonesia’s Academic Dishonesty (‘Joki’), Lack of Merit & Moral Integrity ft. Abigail Limuria (WIUI)”. The data was obtained by selecting statements made by speakers in different instances of the video and transcribing them, followed by a qualitative analysis. The transcription was used as the primary tool, and the analysis was based on the frameworks introduced in Muysken (2000), Poplack (2001), Bullock, Toribio (2009), and Fromkin, Rodman, & Hyams (2014) that considered code-switching and other types of code-mixing as a stratified linguistic strategy that appeared under the influence of context, identity, and meaning. In the seizure of 30 cases of code-switching (15 intra-sentential, 10 inter-sentential, and 5 tag-switching) and 26 cases of code-mixing (12 insertion, 8 alternation, and 6 congruent lexicalization) were found. Such patterns are indications of bilingual proficiency of the speakers as well as the strategic mixing of both English and Indonesian. The reasons are that English is spoken to achieve global or academic clarity, whereas Indonesian provides local cultural coloring and emotional expressivity. By such bilingual acts, the speakers express multilayered meanings, establish a rapport with various groups of people, and reflect their hybrid identities. The present research study shows that linguistic alternations in Indonesian-English dialogical practice not only transfer information through their use, but also entail their social and cultural positioning.